Ghosthunters and the Gruesome Invincible Lightning Ghost! - Funke, Cornelia (Scholastic, 2006)
Hetty Hyssop and her assistant ghosthunters travel to a seaside hotel to investigate the appearance of one of the most dangerous ghosts in the world.